Methodological proposal for the socioecological characterization of family units of production and life in the countryside - Neves, Ana Paula; Ríos-Osorio, Leonardo Alberto; Perez-Cassarino, Julian; Henrique Mayer, Paulo (Revista Mexicana de Ciencias Agrícolas, 2017)
Agricultural research has largely focused on productive and economic aspects of agroecosystems; however, multidisciplinary studies and practices with a focus on complex systems that integrate social and ecological aspects related to production and life in the countriside are required. In this paper, the advances in an integrative methodological proposal under the title of socioecological characterization of family units (CSUF) are shown, in a research oriented to this end, which had a conceptual foundation, the proposition of five methodological phases and its application in a field work in a family unit with milk production in Western Santa Catarina-Brazil, 2013. The concepts of peasant family agriculture, socioecological systems and a complex systems approach, formed the conceptual basis of this research, whose methodological phases were named as follows: collective emergence of the sustainability concept, collective construction of socioecological indicators of local importance, protagonist role of the family, synthesis and feedback. The application of the CSUF using ethnographic instruments had an integrative methodological approach whose objective was to describe the unit collectively, taking into account the points of view of the participants in the study, with whom reflection processes were generated regarding socioecological reality and change perspectives.